2013
DOI: 10.1111/ejn.12395
|View full text |Cite
|
Sign up to set email alerts
|

Task difficulty in mental arithmetic affects microsaccadic rates and magnitudes

Abstract: Microsaccades are involuntary, small-magnitude saccadic eye movements that occur during attempted visual fixation. Recent research has found that attention can modulate microsaccade dynamics, but few studies have addressed the effects of task difficulty on microsaccade parameters, and those have obtained contradictory results. Further, no study to date has investigated the influence of task difficulty on microsaccade production during the performance of non-visual tasks. Thus, the effects of task difficulty on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
134
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 42 publications
(63 reference statements)
12
134
4
Order By: Relevance
“…Similarly, in an oddball paradigm, it is claimed that microsaccade rate might change differentially for odd stimuli in comparison to other stimuli 22,23 , while it has been reported that pupil dilation is also affected by the oddness of a stimulus 8 . Another psychological phenomenon that is linked to changes in pupil diameter and microsaccade rate is cognitive load 24,25 . Here, higher workload is associated with larger pupils and a lower rate of microsaccades 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in an oddball paradigm, it is claimed that microsaccade rate might change differentially for odd stimuli in comparison to other stimuli 22,23 , while it has been reported that pupil dilation is also affected by the oddness of a stimulus 8 . Another psychological phenomenon that is linked to changes in pupil diameter and microsaccade rate is cognitive load 24,25 . Here, higher workload is associated with larger pupils and a lower rate of microsaccades 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Another psychological phenomenon that is linked to changes in pupil diameter and microsaccade rate is cognitive load 24,25 . Here, higher workload is associated with larger pupils and a lower rate of microsaccades 25 . Moreover, also neural correlates of pupil dilation, locus coeruleus (LC), and of microsaccade rate, superior colliculus (SC), are reported to be closely connected 8,18,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Microsaccades also appear to sharpen the perception of edges (Donner & Hemila, 2007), improve spatial resolution (Ko, Poletti, & Rucci, 2010), correct fixation errors related to eye blinks (Costela et al, 2014), enhance visibility for peripheral and parafoveal visual targets (Costela et al, 2013; Martinez-Conde et al, 2006; McCamy et al, 2012), and sample informative regions of natural scenes (McCamy, Macknik, & Martinez-Conde, 2014). Microsaccade dynamics may even offer insight into such states as the viewers attentional level (Engbert & Kliegl, 2003; Yuval-Greenberg, Merriam, & Heeger, 2014) and fatigue (Di Stasi et al, 2013), as well as indicating target detection and the cognitive demands of the task (Otero-Millan, Troncoso, Macknik, Serrano-Pedraza, & Martinez-Conde, 2008; Siegenthaler et al, 2014). Thus, not only are microsaccades relevant to the visual system, they may play a more dynamic, nuanced and neurophysiologically connected role than previously thought.…”
Section: Introductionmentioning
confidence: 99%
“…Orienting is subsumed by parietal areas (Posner & Raichle, 1994) and the frontal eye fields (Corbetta et al 1998). Indeed, attention is related to the control and stabilisation of the eyes and microsaccades (Siegenthaler et al, 2014). Orienting leads to perceptual improvements in many visual tasks.…”
mentioning
confidence: 99%